Kinerja Keuangan Pengaruh Akuntansi Hijau terhadap Nilai Perusahaan di Universitas Muhammadiyah Bengkulu: Tinjauan Literatur Sistematis - Anisya Putri; Dwi Apriliani Ningsih; Nikita Valentin; Yuniarti, Rina (Universitas 45 Surabaya, 2026)
This study comprehensively examines the development of the green accounting concept and the impact of its implementation on financial performance and firm value. Increasing global attention to sustainability issues and environmental responsibility has encouraged companies to integrate environmental aspects into accounting practices and financial reporting as part of their long-term business strategies. The implementation of green accounting is expected not only to contribute to environmental conservation but also to enhance corporate competitiveness and create sustainable value. The research method employed is a Systematic Literature Review (SLR) using a descriptive qualitative approach. The research data are derived from national and international journal articles published during the 2021–2025 period, accessed through Google Scholar and systematically selected based on predetermined inclusion and exclusion criteria. The findings indicate that green accounting is commonly measured using various indicators, such as environmental disclosure based on Global Reporting Initiative (GRI) standards, the recognition and management of environmental costs, green investment, and carbon emission disclosure. The majority of the reviewed studies find that the implementation of green accounting has a positive effect on corporate financial performance, particularly profitability, which ultimately contributes to an increase in firm value. However, several studies also report insignificant or short-term effects, mainly due to the high environmental costs incurred by companies during the early stages of implementation.